The role of polyamines in growth inhibition induced by Momordica charantia and Gynura procumbens in human lung adenocarcinoma cells, A549 - AhmadSujangi, Nurhikmah; Abdullah, Nor Zamzila; Abdul Ghani, Radiah (2016)
Chemoprevention is a crucial process in overcoming the cancer burden throughout the world. By changing dietary choices, people who are at high risk of developing cancer may slow down the carcinogenesis or preventing it altogether. Some food contains high level of polyamine which is bad due to its ability for promoting tumor growth. Hence, this research aimed to determine the polyamine content of selected local plants, Momordica charantia and Gynura procumbens, by using High Performance Liquid Chromatographic (HPLC) analysis as well as conducting cytotoxicity study and growth inhibition study of the plant extracts against the human lung adenocarcinoma epithelial cell lines, A549. The polyamine content of M. charantia was found to be high (more than 200 nmol/g/mol) while G. procumbens contained low level of polyamine (less than 100 nmol/g/ml). Both plants induced cytotoxicity to A549 cells after only 24 hours of exposure to different concentrations of treatment which lead to the establishment of the IC50 at 10.0 mg/ml. Growth curve analysis demonstrated that M. charantia and G. procumbens had successfully reduced the cancer cell progression. On the other hand, there was an increase of intracellular polyamines in the treated cells compared to untreated cells for both M. charantia and G. procumbens. Based on these preliminary findings, it can be concluded that M. charantia and G. procumbens are not an excellent plants to be included in the development of chemoprevention strategy as the ideal chemopreventive agents are those that contain low polyamine level, able to reduce the cancer cell progression and can inhibit the biosynthesis of polyamine in cancer cells to avoid recurrence of cancer. However, further investigation on the effect of these plants on polyamine metabolic pathway and cell death pathway shall be elucidated.